A Phenomenological Study of the Motivation of Freelance Writers in Malang City and Their Life Experience in Surviving Amidst Job and Career Uncertainty - Ahmad Kevin Alfirdaus Arief; Sopiah; Ely Siswanto (ITB AAS INDONESIA Surakarta, 2024)
This phenomenological study explores the motivations of individuals in undergoing a career as a freelance worker in the midst of work and career uncertainty that often characterizes a work environment that has novelty both in technology and in flexibility. This phenomenological study highlights participants' experiences in pursuing a career as a freelancer amidst the uncertainty that often characterizes today's work environment. Through a qualitative approach that explores the direct experiences and thoughts of the research subjects related to what drives them to stay on a freelance path that tends to have no uncertainty. The results show that freelancers' motivations to persist in such uncertain conditions are complex and varied. Some freelancers may be driven by the freedom and flexibility that freelance work brings, while others may seek professional recognition or personal achievement. While others may also be looking to pursue new opportunities and income streams while freelancers are able to work multiple jobs. The research also identified challenges faced by freelancers, including financial uncertainty, pressure to retain clients, and the sense of social isolation that may be felt. In addition, research subjects often highlighted the importance of social support, knowledge of the freelance work method itself, and building a strong professional network.